The Unexplored Benefits of Paediatric Cardiac Humanitarian Work in the Developing World - Nichani, Sahil; Nichani, Sanjiv (Frontiers in Pediatrics, 2021)
Congenital heart disease (CHD) is the most common type of birth defect, significantly affecting children in the developing world. There are 1.35 million children born with congenital heart disease in the world every year with over a million of these children being born in low and middle income countries (LMIC). However, access to care in these regions is severely limited due to poor facilities and insufficient expertise. Consequently, vast numbers of children go years without diagnosis and treatment with disastrous consequences. It is estimated that a million children die every year from untreated heart disease. Humanitarian ventures involving medical teams from the developed world, travel to countries in Asia and Africa attempting to address this problem and provide the poorest of children with potentially life-saving treatment. In this review, we explore the benefits of this work to the travelling medical teams.